Full Day School - What are the Parents’ Expectations? (Training and Practice : Journal of Educational Sciences, 2012)
Full day school is a commonly used form of education abroad. In Hungary it has not been widespread yet, but the debate of the National Curriculum 2012 has attracted a wider interest in the topic. Many new definitions have been created. The full day school is a way of organizing in the school that neither can be made equal to the day – care nor to the extension of morning classes. This form of education has been already present in primary schools, as the classes are followed by writing the homework in the afternoon. This is the time, when there is an opportunity for developing individual competences and talents, doping sports and arts and compensating handicaps. In my research, carried out at the beginning of 2012, I aimed to find out what the parents of 10-14-year-old students expectf rom this new way of education, how they could imagine it in practice and what aims they would pose: whether they regard teaching or education as the primary goal.